If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5g+10=9g
We move all terms to the left:
5g+10-(9g)=0
We add all the numbers together, and all the variables
-4g+10=0
We move all terms containing g to the left, all other terms to the right
-4g=-10
g=-10/-4
g=2+1/2
| 25-4c+12=53 | | -3/5(10d+25)+15=24 | | 12x-6=-36 | | 5r+45=30 | | X+11x+84=180 | | 36x=1/6 | | 5(3x-14)=-100 | | 3/6=x/36 | | -14v=-42 | | -(x-6)-2x=5-4x | | 3+t/(-4)=6 | | X=-4y+5 | | 5b-6=30 | | 5x-23+3x=-7 | | 27(14−28x)=20 | | -19=m/5 | | -16n=96 | | 32.21=6g+3.95 | | 1/5p=39 | | 1-3t^2+3t=0 | | g/4+18=16 | | 189=143-v | | 9-s/3=-6 | | 11x+84=60 | | z/4−2=2 | | 8x+7-3x=5+x+2 | | 4/3t=16 | | 4/3t=18 | | 2/X=X/18x= | | 12.43=2g+3.93 | | 1n-5=5 | | 64.9278(x)+62.9296(1-1x)=63.546 |